Academic productivity and gender at Unesp - Matos, Carlos Alberto O. [UNESP]; Pio, Gabriel A. [UNESP] (Univ Federal Alfenas, 2023)
Unesp's 2021-2024 governance, especially through the Vice-Rector's Office, Dean's Office of Postgraduate Studies and Research, has instituted several awards for teachers, researchers, administrative technicians, undergraduates, postgraduates and post-doctoral students with the objective of recognizing and valuing the role of women in science. The award, as a general rule, emphasizes as its main criteria the relevance of high-impact research and scientific production based on publications in relevant journals. This study aimed to evaluate whether there is a gender-related effect on scientific productivity using the H index, which is one of the main indicators of scientific productivity. Data from 16,753 women and 14,022 men were selected and processed with text mining. The Wilcoxon test rejected H-0 but this result may have been a consequence of the sample size. The results of Exploratory Data Analysis and simulation with resampling techniques using this test and its agnostic version recommend caution in relation to the rejection decision. Finally, ten coefficients that quantify the effect size, tools widely used in Psychology, Medicine and Social Sciences, concluded that this effect, when it exists, can be characterized as negligible.
Keywords: H index; text mining; equity; effect size